Trust in Mass Media and Virtual Social Networks health information: a population study - Mahmoud Tavousi (Payesh, 2019)
Objective (s): Many information sources including mass media provide health information in order to increase awareness and promote peoplechr('39')s health. The aim of this study was to examine people’s trust in mass media and virtual social networks health information. Methods: This cross-sectional study was conducted among a random sample of adults aged 18 to 65 years living in Tehran, Iran. The data were collected using a questionnaire and descriptive statistics were applied to analyze the data. Results: A total of 1174 adults (581 women and 615 men) with a mean age of 37.2 ± 13.02 years and mean education years of 12.5 ± 3.8 years were studied. The highest trust in health information was reported for television (65%) followed by radio (56%). This for social media was 30%. The results obtained from multiple logistic regression analysis indicated that there were no association between trust and demographic variables. However, association between trust and the amount of mass media or social networks use was observed. A unit, increase in the use of mass media and social networks health information increased the odds for trust about 2 to 3.4 times. Conclusion: The study results showed that people’s trust on television and radio for seeking health information was relatively high. This implies that those who provide health for television v and radio have significant responsibility to convey correct information to the public.